THE EFFECT OF VILLAGE FUND ALLOCATION ON POVERTY IN MAIWA DISTRICT (CASE STUDY IN LEBANI VILLAGE AND LABUKU VILLAGE) - Sariana Damis; Nurlaela Kartina (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of village fund allocation on poverty in Maiwa District, especially Lebani Village and Labuku Village. The data collection technique used in this study is documentation. The data used are data realization of village fund allocation, and poverty data with quantitative descriptive analysis techniques using simple linear regression analysis tools with simple regression tests, normality tests, coefficient of determination R2 tests, with hypothesis testing using the T test. Based on the analysis results obtained from SPSS ver22 with a significant value of 0.003 <0.05 which indicated that village fund allocation has a positiveand not significant effect on poverty in the Maiwa District, especially in Lebani Village and Labuku Village. With value coefficient of determination R2 was 8.03%, this means that village fund allocation can affect poverty.